Systematic Reviews of Selected Dental Caries Diagnostic and Management Methods - Bader, James D.; Shugars, Daniel A.; Bonito, Arthur J. (Journal of dental education, 2001)
A systematic review of the English‐language literature was conducted to address three related questions concerning the diagnosis and management of dental caries: a) the performance (sensitivity, specificity) of currently available diagnostic methods for carious lesions, b) the efficacy of approaches to the management of noncavitated or initial carious lesions, and c) the efficacy of preventive methods among individuals who have experienced or are expected to experience elevated incidence of carious lesions. From 1,328 caries diagnostic and 1,435 caries management reports originally identified, thirty‐nine diagnostic studies and twenty‐seven management studies were included in the final evidence tables. Point estimates or reasonable range estimates for the diagnostic validity of methods for the diagnosis of carious lesions could not be established from the literature reviewed. There are insufficient numbers of reports of diagnostic performance involving primary teeth, anterior teeth, and root surfaces. For posterior occlusal and proximal surfaces, quality issues and the variation among studies precludes establishing such estimates. The apparent differences in sensitivity among methods are generally smaller than the variation reported within methods. The literature on the management of noncavitated carious lesions consisted of five studies describing seven experimental interventions. Because these interventions varied extensively in terms of management methods tested as well as other study characteristics, no conclusions about the efficacy of these methods were possible. The literature on the management of individuals at elevated risk of carious lesions consisted of twenty‐two studies describing twenty‐nine experimental interventions. The strength of the evidence for the efficacy of fluoride varnish for prevention of dental caries in high‐risk subjects was fair, and the evidence for all other methods was incomplete. Because the evidence for efficacy for some methods, including chlorhexidine, sucrose‐free gum, and combined chlorhexidine‐fluoride methods, is suggestive but not conclusive, these interventions represent fruitful areas for further research.